Genome-wide identification and characterization of the fibrillin gene family in Triticum aestivum - Yaoyao Jiang; Haichao Hu; Yuhua Ma; Junliang Zhou (PeerJ, 2020)
Background The fibrillin (FBN) gene family is highly conserved and widely distributed in the photosynthetic organs of plants. Members of this gene family are involved in the growth and development of plants and their response to biotic and abiotic stresses. Wheat (Triticum aestivum), an important food crop, has a complex genetic background and little progress has occurred in the understanding of its molecular mechanisms. Methods In this study, we identified 26 FBN genes in the whole genome of T. aestivum through bioinformatic tools and biotechnological means. These genes were divided into 11 subgroups and were distributed on 11 chromosomes of T. aestivum. Interestingly, most of the TaFBN genes were located on the chromosomes 2A, 2B and 2D. The gene structure of each subgroup of gene family members and the position and number of motifs were highly similar. Results The evolutionary analysis results indicated that the affinities of FBNs in monocots were closer together. The tissue-specific analysis revealed that TaFBN genes were expressed in different tissues and developmental stages. In addition, some TaFBNs were involved in one or more biotic and abiotic stress responses. These results provide a basis for further study of the biological function of FBNs.